Dominica : Statistical Annex. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
In this study, the following statistical data are presented in detail: GDP at constant factor cost, saving and investment, selected agricultural production, selected industrial production, consumer price indices, summary accounts of the consolidated public sector, central government expenditure, monetary survey, gross public sector debt, selected interest rates, consolidated balance sheet of the major credit unions, balance of payments, expenditure on the public sector investment program, accounts of rest of the general government, direction of trade, imports by product type, and so on.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy